Hubungan Demografi Tenaga Kefarmasian terhadap Patient safety di Rumah Sakit Islam Sultan Agung Kota Semarang - Meki Pranata; Zulfa Maria Qibtiyah; Chilmia Nurul Fatiha (Fakultas Farmasi Universitas Pancasila, 2022)
Patient safety is a fundamental element in providing patient care and is a component of patient rights. Pharmaceutical services are one aspect of patient safety implementation. Patient safety is a variable used to monitor and evaluate the service quality of pharmacy staff in hospitals. This study aims to determine the relationship between the demographic characteristics of pharmaceutical personel with the implementation of patient safety at the Sultan Agung Islamic Hospital, Semarang City. This research is an analytic observational study using a cross sectional design. The research subjects who met the inclusion criteria were 39 pharmacists. Data collection was carried out in November 2020 using a questionnaire adapted from 6 patient safety aims by the 2018 National Hospital Accreditation Standard (SNARS) edition 1.1. Data analysis using Spearman's-Rho and Eta correlation test. The results of research conducted from 39 respondents showed that the implementation of patient safety has been carried out properly. This is due to there was a demographic correlation on patient safety including length of work for patient safety of 0.672 and a weak correlation between age and education status on the implementation of patient safety at the Sultan Agung Hospital, Semarang. The correlation coefficient values are 0.238 and 0.370 with a significance value of p<0.05. There is a significant relationship between length of work and the application of patient safety and there is no significant relationship between gender, profession, marital status, age, last education and place of work with a significance of p> 0.05.